Peran Ombudsman Sebagai Lembaga Pengawasan Pelayanan Publik Di Kabupaten Halmahera Selatan Provinsi Maluku Utara - Sukur Suleman; Marno Wance (Universitas Muhammadiyah Ponorogo, 2020)
This research was conducted by looking at the condition of public service in South Halmahera Regency which always expands various problems both public services, public goods and public administration, besides that the role of the ombudsman as an oversight agency for public services is also still weak. Therefore, the task and authority of the Ombudsman in South Halmahera Regency is a study in order to address the existing maladministration issues. This study aims to determine the North Maluku Ombudsman in carrying out its role as a public service supervision institution in South Halmahera Regency, then to examine what are the determinant factors of the North Maluku Ombudsman in carrying out its role as a supervisor in South Halmahera Regency. This research uses a qualitative approach to the type of case study (case study). Data used through observation, interviews and documentation. The results showed that the role of ombudsmna in South Halmahera Regency was not maximal, as seen from the process and stages of receiving reports, clarification, infestigation, mediation and recommendations, then the low level of innovation carried out, both socialization, cooperation, then its human resources, supporting facilities, budget and knowledge Public.